Cultures and Works of Tay People Through Vocative Words - Duong Thi Ngu; Pham Thi Huyen Trang; Le Thi Han; Pham Thi Hong Nhung (Borong Newinera Publisher, 2022)
Culture has a close relationship with many fields, including Linguistics. Language is a special product of culture. It is a means of communication and a tool for thinking. Language is a means to reflect, maintain and develop culture. Any meaningful sign of a language contains a cultural element. Vocative words are one of those cases. The article explores the vocative words system in the language of the Tay people in Tuyen Quang Province, Vietnam and concludes that culture is not only a factor that generates language, but also an environment for language to exist and develop. develop. Through the system of vocative words in the Tay language, it shows the cultural characteristics of respect affection of the Tay people.